Actual problems of exposure risk assessment of finely dispersed aerosols and aerosols of nanoparticles - Sevalnev, A. I.; Sharavara, L. P.; Nefedov, O. O.; Nefedova, O. O.; Shatorna, V. F.; Севальнєв, Анатолій Іванович; Шаравара, Лариса Павлівна; Нефьодов, О. О.; Нефьодова, О. О.; Шаторна, В. Ф.; Севальнев, А. И.; Шаравара, Л. П.; et al. (Запорізький державний медичний університет, 2018)
Purpose of the study – analysis of the scientific literature on generalization of the data on domestic and foreign experience in risk assessment due to exposure to finely dispersed aerosols and aerosols of nanoparticles (NPs). The article summarizes data of long-term studies on the effect of nanomaterials and nanoparticles on the quality of human habitat and health. The domestic and foreign experience of harm health assessment, safety of new types of nanomaterials for the environment and work-related conditions have been analyzed.There are numerous studies of foreign and domestic scientists on the biological activity of nanoparticles and their effect on experimental animals, namely, on the specificity of their effect on various organs and systems of the body. Classification of nanomaterials, depending on their chemical composition, is presented. Attention is paid to the problems of nanosafety, namely, to the evaluation of nanotoxicity of substances and to the definition of the concept of a “dose” for nanoparticles. The data on the presence of finely dispersed and ultra-fine particles in the atmospheric air, which increase risk of respiratory system diseases among residents of large megacities, is given. There is special importance on assessing work conditions and occupational risks in production and use of materials which contain nanoparticles as well as in production processes with formation of the fine dust and nanoparticles indicated in the article. Due to the lack of a clear system for assessing health risks related to the action of nanoparticles, lack of common criteria of harmfulness and maximum allowable concentrations for most nanoparticles and uniform methods of their control, it is suggested to strictly adhere to protective measures in contact with nanomaterials and active improvement of nanosecurity measures. Conclusions. High toxicity and health hazards of finely dispersed and ultra-fine particles confirm need to control their content in the air of the populated areas and in the air of the working zone of industrial enterprises, where suspended particles are formed in the technological process. Obtained results of the scientific studies should be used for substantiation of preventive measures on nanosecurity in development and implementation of the nanotechnology, in order to protect health of workers and the general population. Цель работы – анализ научной литературы для обобщения данных об отечественном и зарубежном опыте оценки риска от воздействия высокодисперсных аэрозолей и аэрозолей наночастиц. Обобщены материалы многолетних исследований воздействия наноматериалов и наночастиц на качество среды обитания человека и на его здоровье. Проанализирован отечественный и зарубежный опыт оценки вреда здоровью, безопасности новых видов наноматериалов для окружающей и производственной среды. Представлены многочисленные исследования зарубежных и отечественных ученых биологической активности наночастиц и их влияния на экспериментальных животных, а именно особенности их воздействия на различные органы и системы организма. Представлена классификация наноматериалов в зависимости от химического состава. Уделено внимание проблемам нанобезопасности, а именно оценке нанотоксичности веществ и определению понятия «доза» для наночастиц. Приведены данные о наличии в атмосферном воздухе мелкодисперсных и ультратонких частиц, которые повышают риск заболеваний респираторной системы у жителей мегаполисов. Указана особая важность оценки условий труда и профессионального риска при производстве и применении материалов, содержащих наночастицы, а также производственных процессов с образованием мелкодисперсной пыли и наночастиц. В связи с отсутствием четкой системы оценки рисков для здоровья от действия наночастиц, единых критериев вредности и предельно допустимых концентраций для большинства наночастиц и единых методов их контроля, предлагается более строгое соблюдение мер защиты при контакте с наноматериалами и активное совершенствование мероприятий по нанобезопасности. Выводы. Высокая токсичность и опасность для здоровья мелкодисперсных и ультратонких частиц подтверждает необходимость организации контроля их содержания в воздухе населенных мест и в воздухе рабочей зоны промышленных предприятий, в технологическом процессе которых образуются взвешенные частицы. Полученные результаты научных исследований необходимо использовать для обоснования профилактических мер нанобезопасности при разработке и реализации нанотехнологий для охраны здоровья работающих и населения в целом. Мета роботи – аналіз наукової літератури для узагальнення відомостей про вітчизняний і закордонний досвід оцінювання ризику від впливу високодисперсних аерозолів та аерозолів наночасток. Узагальнили матеріали багаторічних досліджень впливу наноматеріалів і наночастинок на якість середовища проживання людини та на її здоров’я. Проаналізували вітчизняний і закордонний досвід оцінювання шкоди для здоров’я, безпеки нових видів продукції наноматеріалів для довкілля та виробничого середовища. Наведені численні дослідження закордонних і вітчизняних учених щодо біологічної активності наночастинок і їхнього впливу на експериментальних тварин, зокрема особливості впливу на різні органи, системи організму. Подано класифікацію наноматеріалів залежно від хімічного складу. Приділено увагу проблемам нанобезпеки, зокрема оцінюванню нанотоксичності речовин і визначенню поняття «доза» для наночастинок. Наведені відомості щодо наявності в атмосферному повітрі дрібнодисперсних, ультратонких частинок, які підвищують ризик захворювань респіраторної системи в жителів мегаполісів. Наголошено на особливій важливості оцінювання умов праці та професійного ризику під час виробництва й застосування матеріалів, що містять наночастинки, а також виробничих процесів з утворенням дрібнодисперсного пилу та наночастинок. У зв’язку з відсутністю чіткої системи оцінювання ризиків для здоров’я від дії наночасток, єдиних критеріїв шкідливості та гранично допустимих концентрацій для більшості наночастинок та єдиних методів їх контролю запропоновано чітке дотримання методів захисту під час контакту із наноматеріалами та активне вдосконалення заходів із нанобезпеки. Висновки. Висока токсичність і небезпека для здоров’я дрібнодисперсних та ультратонких частинок підтверджує необхідність організації контролю їх вмісту в повітрі населених пунктів і повітрі робочої зони промислових підприємств, у технологічному процесі яких утворюються зважені частинки. Результати наукових досліджень необхідно використовувати для обґрунтування профілактичних заходів нанобезпеки під час розробки та реалізації нанотехнологій для охорони здоров’я працівників і населення загалом.
Актуальні питання оцінювання ризику впливу високодисперсних аерозолів та аерозолів наночасток
Актуальные вопросы оценки риска воздействия высокодисперсных аэрозолей и аэрозолей наночастиц
Keywords: nanoparticles; finely dispersed particles; working zone air; occupational risk; наночастицы; мелкодисперсные частицы; воздух рабочей зоны; профессиональный риск; наночастки; дрібнодисперсні частки; повітря робочої зони; професійний ризик